Seasonal Variations Of Nutrients In Perur Chettipalayam Lake, Coimbatore District, Tamilnadu, India - M, Lekeshmanaswamy; K, Anusiyadevi (Kongunadu Research Journal, 2019)
The water quality was performed in Perur Chettipalayam Lake, Coimbatore District from July 2015 to June 2016, with specific regard to nutrient content. The nutrients investigated were phosphate, calcium,magnesium, chlorides, nitrates and sulphates. The obtained results showed marked seasonal changes in contamination of the sewage pond. The analyzed nutrient content shows that the lake is extremely contaminated with sewage.